Evaluation of Biodegradable Floating Grow Mat Materials for Hydroponically Grown Lettuce (Lactuca sativa) - Tamayo Gutiérrez, Evelin Alexandra (2020)
This study proposes an alternative biodegradable material for use with lettuce crops utilizing the bare-root hydroponic system, with the aim of functionally replacing expanded polystyrene, commonly used as a supporting material despite being a highly contaminating substance. This proposal is based on the production of individual pieces of floating material made from agro-industrial waste with an organic wax waterproof coating. The materials were produced in Quito, Ecuador, and the variables analyzed were hardness, compressive strength, flexural strength and microbiological contamination of the material during the vegetable growing period. Results showed that the alternative substrate with the greatest adaptability to the crops was made from a carnauba wax-coated palm fiber (Elaeis guineensis) blended with rice, in a ratio of 70%-30%, respectively.